Job Insecurity and Subsequent Actual Turnover: Rumination as a Valid Explanation? - Richter, Anne; Vander Elst, Tinne; De Witte, Hans (Frontiers in Psychology, 2020)
Job insecurity is a work stressor with many negative consequences for the individual as well as the organization. However, currently, little is known about why job insecurity is related to these outcomes. In the present study, actual turnover was investigated as a possible consequence of job insecurity. Additionally, rumination about a possible job loss (i.e., the act of intensified thinking about the future of the job) was investigated as an explanatory mechanism. Relationships were tested using longitudinal data from a sample of 699 Belgian employees. Results of structural equation modeling analyses show that job insecurity was related to turnover one year later. This relationship was mediated by rumination about job insecurity. Actual turnover was investigated over time as a potential consequence of job insecurity, compared to many studies that used turnover intention as a proxy to predict actual turnover. Moreover, a job insecurity-specific mechanism—namely, rumination about job insecurity—was studied, which increased our understanding of how job insecurity develops into its consequences.